Changes of Planning Strategies in Forestry Sector in Tamil Nadu - Dey, Gautam; Sarcar, Manoj Kumar (Indian Forester, 1998)
Tamil Nadu has fairly broad spectrum and 42 types of forests containing rich variety of flora and fauna are found in the State. The Government of Tamil Nadu formulated and implemented many schemes for conservation, development and production in forestry sector. It has changed the planning process and planning strategies have shifted from mere raising of plantations to that of a holistic approach of biodiversity conservation involving Joint Forest Management. The objectives and approaches of different Five Year Plans have been highlighted.